Prediction of Days in Hospital Dengue Fever Patients using K-Nearest Neighbor - Putri Wulandari, Dewa Ayu; Budi Permana, Kadek Ary; Sudarma, Made (International Journal of Engineering and Emerging Technology; Vol 3 No 1 (2018): January - June, 2018)
Dengue fever is found more in tropics and subtropics area. The World Health Organization (WHO) noted that Indonesia is as the highest dengue fever cases in South Asian since 1968 till 2009. The treatment of patient dengue fever in hospital had spent rest time or the days in hospital in variation treatment. Days in hospital often becomes questions from the patients’ family. To predict of days in hospital is maybe to know the capacity for the long period strategies. In this research, we used machine learning approach to predict the period of dengue fever patients. One of the machines of learning method is KNearest Neighbor (K-NN). In this case, we analyze the result of implementation K-NN method that used to predict period of days in hospital patients for dengue fever. This paper used the result of laboratory checking of blood complete with patients as parameter in predict the period of days in hospital dengue fever. The result of examination used K-NN to show the accuracy levels reach 65,67% with k optimal is k =13.